Assessing the Online Purchasing Behavior during the Covid-19 Pandemic: A Case Study in the Kingdom of Bahrain - Mohamed Khalifa Al-Khalifa; Muhammad Rizky Prima Sakti; Abdullah Alhadrami (Global Review of Islamic Economics and Business, 2021)
The Covid-19 pandemic has disrupted consumer habits of buying and shopping. It is anticipated that online purchasing transactions are increased during the pandemic, since the consumers are urged to stay home and practice new normal behavior. This study examines the online purchasing transactions in the Kingdom of Bahrain during the pandemic. Particularly, the study investigates the impacts of product price, product availability, social media, product details, and easiness toward online purchasing decision during Covid-19 pandemic. Using hand-collected data from 200 respondents, the study discovers that all variables have significant impacts toward online purchasing behavior in the Kingdom of Bahrain during the pandemic age.